Chaotic Stream Cipher-Based Secure Data Communications over Intelligent Transportation Network. (1st March 2015) - Zhang, Wei; Tang, Shanyu; Zhang, Liping; Ma, Zhao; Song, Jun
Abstract : Intelligent transportation systems (ITS) are advanced applications in which the transportation industry is adapted to the information technology revolution. As an important development direction of ITS, the electronic toll collection (ETC) subsystem, which enables an efficient and speedy toll collection, has gained widespread popularity in the world. In an ETC system, toll transaction data are transmitted over intelligent transportation networks, which is vulnerable to eavesdropping, interfering, and tampering attacks. To address the above security problems, we proposed a chaotic stream cipher-based cryptographic scheme to realise secure data communications over wireless sensor network (WSN), which is a part of ITS. The proposed cryptographic scheme allowed ITS to achieve key negotiation and data encryption between sensor nodes in the WSN, whileas reduced computational costs and power consumption. Security analysis and experimental results showed that the proposed scheme could protect data transmission between wireless sensor nodes from being attacked, and significantly reduced the communication overhead for the whole system compared to the existing ECC_AES scheme, thus satisfying the real-time data transmission requirement of ITS.